Fruity Cafe / Munirah Shaim... [et al.] - Shaim, Munirah; Arzmi, Mas Ayu; Reuben, Erica Joanne; Ramlee, Nur Afiqah; Ismail, Siti Ishmanisa (2016)
Producing and selling healthy fruit drinks in which we are using fresh fruits such as dragon fruit, banana, durian, honey dew, watermelon, papaya and many more. The uniqueness of our fruit drinks is we add the "sunnah foods" such as raisins, dates and many more as the toppings and we did not use any sugar in the juice.